Mercury in soils impacted by alluvial gold mining in the Peruvian Amazon - Velásquez Ramírez M.G. (2021)
Gold mining is the largest source of mercury (Hg) pollution worldwide. The discharge of mercury in the environment bears direct human health risks and is likely to increase cascading effects throughout local food chains. In the Peruvian Amazon the mining process consists of slashing and burning trees, followed by extraction of gold-bearing sediment, amalgamation with Hg and gold recovery, leading each year to the degradation of 6,000-10,000 ha and the release of 180 metric tons of Hg per year to the enviroment. The purpose of this study was to determine soil Hg levels in soils of abandoned alluvial gold mine spoils and undisturbed forest in the Madre de Dios region, the epicenter of alluvial gold mining in Peru. We selected gold mine spoils of the two most important technologies locally applied for gold extraction, i.e., Minimally Mechanized Mining (MMM) and Highly Mechanized Mining (HMM), in the native communities of Laberinto and Kotzimba, respectively. We collected 127 and 35 soil samples (0-20cm depth) from potentially contaminated sites and undisturbed forest, respectively. Physicochemical analysis and determination of Hg levels were determined for all soil samples. None of the samples had Hg concentrations above Peruvian, Canadian and British Environmental Quality Standards for Agricultural Soil (6.6mg/kg). Hg levels in MMM and HMM were not significantly different between the two areas. The main variables explaining variation of soil Hg concentrations were the vegetation cover, soil organic matter, soil pH and clay particle content, which explained up to 80% of data set variation. Surprisingly, highest Hg concentrations were found in untouched old-growth forest bordering the mine spoils, but there was also a trend of increasing Hg concentrations with the regenerating vegetation. Our findings suggest that Hg concentrations in old mine spoils are low and shouldn't stand in the way of efforts to restore soil conditions and develop sustainable land uses. However, it is urgent to end the use of Hg in mining operation to decrease human and environmental risks. © 2021 Elsevier Ltd